2009
DOI: 10.1063/1.3098408
|View full text |Cite
|
Sign up to set email alerts
|

Improved leakage and ferroelectric properties of Mn and Ti codoped BiFeO3 thin films

Abstract: Polycrystalline BiFeO 3 ͑BFO͒, Ti-doped BFO, Mn-doped BFO, and ͑Mn, Ti͒-codoped BFO ͑BFMT͒ thin films were fabricated on Pt/ SrTiO 3 ͑100͒ substrate by pulsed laser deposition. Observed leakage current behavior in those ion-doped BFO films indicated the dominance of space-charge-limited current in the high electric field region. The leakage current of the BFMT film was much reduced in relation to the other films due to the formation of deep traps. In the BFMT film, well saturated P-E hysteresis curves were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
102
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(110 citation statements)
references
References 17 publications
(30 reference statements)
5
102
2
1
Order By: Relevance
“…Many research groups have reported that a site-engineering technique using various elements is effective to suppress the leakage current in BFO films. [11][12][13][14][15][16] We proposed (Nd,Mn)-codoped BFO (BNFM) and (Pr,Mn)-codoped BFO (BPFM), and succeeded in obtaining improved electrical properties. 14,[17][18] Recently, polarization-induced photovoltaic properties in BFO films have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Many research groups have reported that a site-engineering technique using various elements is effective to suppress the leakage current in BFO films. [11][12][13][14][15][16] We proposed (Nd,Mn)-codoped BFO (BNFM) and (Pr,Mn)-codoped BFO (BPFM), and succeeded in obtaining improved electrical properties. 14,[17][18] Recently, polarization-induced photovoltaic properties in BFO films have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In the last several years, many research groups have reported that a siteengineering technique is effective to solve this problem 12) 33) because the leakage current of BFO thin films is mainly caused by the nonstoichiometric compositions or impurity phases in the film.…”
Section: Introductionmentioning
confidence: 99%
“…The decreasing current density caused by Mn 3+ doping was already reported for BFO films with somewhat different behaviors. 10,25,26) That is, J values of the Mn 3+ -doped films were higher than those of undoped films in a low E region but they became smaller at higher E as a result of reduced rates of the increasing J. Mn 3+ doping in this study, however, resulted in reduced J values of the doped BFO samples even in a low E region. From a linear relationship in the log (J) vs log (E) plot for the 5%Mn 3+ -doped and undoped BFO ceramics, the slopes  in an expression J  E  were evaluated to be   1.4 and   2.4, respectively.…”
Section: +mentioning
confidence: 42%